Effect of Annealing on the Electrical and Optical Properties of MgZnO Films Deposited by Radio Frequency Magnetron Sputtering. Issue 14 (29th January 2020) - Kushimoto, Maki; Sakai, Tadayoshi; Ueoka, Yoshihiro; Tomai, Shigekazu; Katsumata, Satoshi; Deki, Manato; Honda, Yoshio; Amano, Hiroshi
Abstract : The properties of phase‐separated MgZnO induced by heat treatment are investigated, because the electrical conductivity of MgZnO deposited by sputtering can be improved by heat treatment. The absorption edge shows a red shift, but the transmittance in the ultraviolet (UV)‐C region increases after heat treatment. This is due to the formation of wurtzite (WZ) MgZnO with a high Zn content and a rock salt (RS) structure with a low Zn content induced by phase separation. This suggests that the current path is formed by the WZ crystals with low resistivity, and the transmittance in the UV region is increased by the RS crystals with high transmittance. It is confirmed that the RS structure is partially mixed with the WZ crystal in the in‐plane direction. In contrast, different distributions of crystals are observed in the stacking direction. A WZ structure is formed after RS‐MgZnO is formed on the substrate interface. It is found that Mg is incorporated into the RS structure by heat treatment, and Mg‐rich MgZnO is formed. Abstract : The properties of phase‐separated MgZnO induced by heat treatment are investigated to improve the electrical conductivity of MgZnO deposited by sputtering. The results suggest that the current path is formed by WZ crystals with low resistivity, and the transmittance in the ultraviolet region is increased by the RS crystals with high transmittance.